Faktor Faktor Yang Mempengaruhi Peran DPRD Dalam Pengawasan Keuangan Daerah - Simson Werimon; Memed Ronsumre; Hustianto Sudarwadi (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2019)
This study aims to examine the influence of personal background, political background and knowledge of council about budget towards the role members of DPRD on financial region supervision. This research is motivated by the fact individual backgroundwill effect to individual behavior for their role and on political activity. Dependent variable in this research are the role members of DPRD on financial region supervision. Independent variables are personal background, political background and knowledge of council about budget. The data in this research consist of primary data that taken from questionnaires distributed directly to respondents. The collected are from 43 respondents that members of DPRD at West Papua Province. Hipothesis of this study are examine by using Multiple Linear Regression use SPSS 22 program. The result of this indicated that‟s, first, there is a positive influence of personal background toward the role members of DPRD on financial region supervision. Second, political background haven‟t effect towards the role members of DPRD on financial region supervision. Third, knowledge of council about budget affect towards the role members of DPRD on financial region supervision. The suggestions for further research, research instrument of variable education and trainning, organizational experience, experience in DPRD should be developed. Measurement of variable length of employment in government should be developed.